The Influence Of Product Quality And Brand Image On Purchase Decision Of Indosat Card Users With Customer Trust As An Intervening Variable (Case Study of Economics Faculty Students University Sarjanawiyata Tamansiswa Yogyakarta) - Cecep Aditiya; Nonik Kusuma Ningrum; Putri Dwi Cahyani (UNIVED Press, 2024)
The aim of this research is to test and explain the influence of product quality and brand image on Indosat card users' purchase decisions with customer trust as an intervening variable. This research was conducted on students at the Faculty of Economics, Bachelorwiyata Tamansiswa University using the Slovin formula with a sample size of 100 respondents who used statements each variable via Google from to share with students. The research results show that product quality has a positive and significant influence on customer trust, the influence of brand image has a positive and significant influence on customer trust, product quality has no significant influence on purchase decisions, brand image has a positive and significant influence on purchase decisions, and customer trust has a positive and significant influence. significant impact on purchase decisions.